Prevalence of Colibacillosis in Goat Kids in Udaipur district of Rajasthan - Sharma, Shiv Kumar; Manat, Naina; Joshi, Monika (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Colibacillosis is an economically important disease of goat kids. In the present study, total 126 goat kids up to 3 months of age were  screened to find out prevalence of colibacillosis in Udaipur district of Rajasthan. The overall prevalence of colibacillosis in goat kids up  to 3 month of age was found to be 17.46 percent (22/126). The occurrence of colibacillosis among 70 diarrhoeic kids was found to be  31.43% (22/70). There was highly significant difference in the prevalence of colibacillosis in goat kids in different age groups (P >0.05).  The prevalence of colibacillosis was found decreasing with the increase of the age in the kids. The prevalence of colibacillosis was  significantly higher in female kids than male kids. (P ≤0.05).
Keywords: Colibacillosis; Goat kids; Prevalence; Udaipur district